Academic Senate Minutes 2012-03-22 - Academic Senate:::::::::
Revision to MS Family Nurse Practitioner program and Revisions to the Theater Arts program - approved. Information Item: Revised Student Fee Referendum Code. Replacement of existing policy with new Sabbatical and Difference in Pay (DIP) policies amended and approved. Theater Arts invitation to collaborate in themed year 2012 -2013.